PENERAPAN METODE SOSIODRAMA BERMEDIA BANDO DESA UNTUK MENINGKATKAN HASIL BELAJAR DAN LEADERSHIP SKILL - Oktiani, Ega; Hanifah, Nurdinah; Nur Aeni, Ani (Jurnal Pena Ilmiah, 2017)
Based on the observation data foundÂ  problems which has associated with result of study and skill of leadership, it was because of learning process used only conventional method, so the results of the study under KKM. From the first learning outcomes data obtained 14,28 of students who had been completed and 85,71 percent of students that have not been solved .From the fact that was certainly there should be a change of learning by doing research the act of a class ( PTK ) with Kemmis and MC Taggart design by applying the sociodrama method .The instruments of this research are guidelines for observation is placed on teacher performance, the activity of students , interview guidelines were teachers and students, and test learning outcomes. From the research been an increase in performance of teachers in the planning stage cycle I obtain the percentage of 88 %, the cycle II 96 % and cycle III 100 percent, is placed on teacher performance in the implementation stage obtain the percentage of 86 %, the cycle II 93 percent, and the cycle III 100 percent, and also on the activity of students cycle all the aspects I leadership skill obtain the percentage of 70 %, the cycle II 73 %, cycle III 85,71 %, and learning outcomes obtain the percentage increased to 33 %, increased to 57 % in the cycle II and increased to 90 percent in the cycle III .Thus the application of a method of sociodrama with bando desa media can increase learning outcomes and leadership skill at fourth grade SDN Legok II .